Hidden Role of Trophic Cascade Effects for Soil Carbon Sequestration in Alpine Tundra - Xinchang Kou; Ziwei Wang; Yan Tao; Yakov Kuzyakov; Shengzhong Wang; Ziping Liu; Haitao Wu; Hong S. He; Haibo Du; Mai‐He Li (Global Change Biology, 2026)
Large soil organic carbon (SOC) stocks in alpine tundra play a critical role in the global carbon budget but are increasingly vulnerable to loss under climate warming. These losses are partly driven by vegetation shifts, such as the upward migration of herbaceous plants, which alter soil food web structure and influence SOC sequestration. Although interactive effects between these processes are expected, they remain largely unclear or hidden. Here, we conducted a 13 C‐labeled glucose tracing experiment in the alpine tundra of Changbai Mountain to investigate how upward migration of Deyeuxia angustifolia affects soil food web structure, energy flows, and ultimately SOC sequestration. Compared with soils without migration (NM), heavily herb‐migrated (HM) soils showed intensified carbon fluxes within trophic cascade, increasing carbon transfer to higher trophic levels, including fungivores, omnivores‐predators, plant‐parasites, meso‐ and macrofauna. Predators in HM soils progressively increased 13 C assimilation over the 30‐day period, while microbivores showed a 5‐day lag behind microbial 13 C uptake. This predator‐driven energy dissipation was 2–14 times greater in HM than in NM soils and constituted an inefficient carbon sequestration pathway that limited the formation of stable carbon pools. As a result, SOC turnover in HM soils was more than 50% lower than in NM soils, indicating a shift toward less stable organic matter forms and reduced net carbon accumulation. Overall, our findings demonstrate that soil food webs play a pivotal role in both “belowground shaping” and “aboveground feedback” processes during herbaceous plant migration and that strengthened trophic cascade effects redirect carbon flow toward inefficient pathways, thereby constraining SOC sequestration in alpine tundra ecosystems.